2022
DOI: 10.1080/21655979.2021.2008667
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Saxagliptin enhances osteogenic differentiation in MC3T3-E1 cells, dependent on the activation of AMP-activated protein kinase α (AMPKα)/runt-related transcription factor-2 (Runx-2)

Abstract: Osteoporosis is a metabolic bone disease commonly observed in the elderly, and its pathogenesis is associated with declined osteogenic differentiation. Osteogenic differentiation could be facilitated by the activation of the AMP-activated protein kinase (AMPK) pathway. Saxagliptin, an anti-diabetic agent with inhibitory effects against dipeptidyl peptidase 4 (DPP-4), has been recently reported to induce the activation of the AMPK pathway. The present study proposes to explore the function and mechanism of Saxa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 42 publications
(41 reference statements)
0
16
0
Order By: Relevance
“…OPN is an osteogenic marker of osteoblast mineralization and maturation. In addition, OCN is identified as an osteogenic marker of terminal stage in osteoblasts. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…OPN is an osteogenic marker of osteoblast mineralization and maturation. In addition, OCN is identified as an osteogenic marker of terminal stage in osteoblasts. …”
Section: Resultsmentioning
confidence: 99%
“…In addition, the graphene has a large specific surface area and there are some wrinkles and ripples on the surface of graphene, which could sustain lateral stresses that might affect cytoskeletal tension. , This leads to changes in cytoskeletal organization/structure and induces cell differentiation . Obtained by SPS, composite particles have a strong noncovalent binding capacity and act as preconcentrators for chemicals, resulting in proteins and growth factors accumulate on their surface for osteogenic inducers, accelerating the differentiation progression of MSCs to the osteogenic lineage . The surface of GNPs flakes in the particles obtained by ultrasound treatment was mostly covered by ECPP particles and therefore could not absorb the molecules directly.…”
Section: Resultsmentioning
confidence: 99%
“…Osteoblast differentiation and mineralization are important stages in bone formation [ 21 , 22 ]. Emerging factors participates in this process of bone formation and regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…AMP-activated protein kinase (AMPK) regulates the differentiation of osteoblasts and bone formation ( Li et al, 2018 ). It has been demonstrated that the activation of the AMPK/Runx2 pathway is an important mechanism underlying the facilitating effects of agents against osteogenic differentiation in MC3T3-E1 cells ( Wang Q. et al, 2022 ). Thus, whether Exo-Ica enhances osteogenic differentiation in MC3T3-E1 cells by regulating the AMPK-α/Runx2 pathway may be an interesting direction in the next studies.…”
Section: Exosomes As Delivery Vehicles For Compounds Isolated From Tcmmentioning
confidence: 99%